Emergency Education Principles Child Friendly Based in Sister Village System Implementation (Mitigation of Mount Merapi Eruption Disaster) - Aulia Puspita Saputri; Kanthi Pamungkas Sari (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Emergency education is held when a disaster occurs and is intended for children affected by the disaster. The implementation should be child-friendly so that the child's psychological condition is not disturbed or depressed. But in reality, many are held spontaneously and are influenced by external factors. This study aims to examine the principles of emergency education that is implemented on a child-friendly basis in the implementation of the sister village system (Mitigation of the Mount Merapi eruption disaster). The research method used is qualitative, with data collection techniques using FGD, interviews and observations. The research subjects were 15 volunteers from the Merapi Emergency School volunteers, Al Qur'an Education Park, the Krinjing Village Disaster Risk Reduction Organization and the Village Disaster Management Institute. Meanwhile, the informants were children who were affected by the eruption of Mount Merapi from Krinjing Village, Dukun District, who lived in the Deyangan Village Refugee Command Post and the Deyangan Village Refugee Post Coordinator. The object of the research is the implementation of all the principles of emergency education for children living in the Deyangan Village Refugee Post in the implementation of the sister village system. Data analysis techniques with data collection, data presentation, data reduction, verification / drawing conclusions. The results showed that the emergency education held had implemented child-friendly principles, namely non-discrimination, activities oriented towards fulfilling the best interests of children, creating an environment that respects children's dignity and ensures holistic and integrated development, respect for children's views, good education management.